Renin-Angiotensin Activation and Oxidative Stress in Early Heart Failure with Preserved Ejection Fraction - Negi, Smita I. (Biomed Res Int, 2015)
Animal models have suggested a role of renin-angiotensin system (RAS) activation and subsequent cardiac oxidation in heart failure with preserved ejection fraction (HFpEF). Nevertheless, RAS blockade has failed to show efficacy in treatment of HFpEF. We evaluated the role of RAS activation and subsequent systemic oxidation in HFpEF. Oxidative stress markers were compared in 50 subjects with and without early HFpEF. Derivatives of reactive oxidative metabolites (DROMs), F2-isoprostanes (IsoPs), and ratios of oxidized to reduced glutathione (E (h) GSH) and cysteine (E (h) CyS) were measured. Angiotensin converting enzyme (ACE) levels and activity were measured. On univariate analysis, HFpEF was associated with male sex (p = 0.04), higher body mass index (BMI) (p = 0.003), less oxidized E (h) CyS (p = 0.001), lower DROMs (p = 0.02), and lower IsoP (p = 0.03). Higher BMI (OR: 1.3; 95% CI: 1.1–1.6) and less oxidized E (h) CyS (OR: 1.2; 95% CI: 1.1–1.4) maintained associations with HFpEF on multivariate analysis. Though ACE levels were higher in early HFpEF (OR: 1.09; 95% CI: 1.01–1.05), ACE activity was similar to that in controls. HFpEF is not associated with significant systemic RAS activation or oxidative stress. This may explain the failure of RAS inhibitors to alter outcomes in HFpEF.